Development and validation of questionnaire to assess knowledge, attitude and awareness about stroke among young population - Gujar, Aakanksha A.; Kumar, Sanjiv (International Journal of Research in Medical Sciences, 2025)
Background: Stroke is a neurological condition which is caused by disturbed blood supply to the brain, causing mental, physical and social impairment. Stroke prevalence in young individuals is rising globally, as well as in India. The young population is still ignorant about stroke and thinks of it as an illness of the elderly. Due to lack of understanding and education about ailment, one contributing aspect maybe one’s attitude towards the condition. Considering these factors this questionnaire was developed. Method: The knowledge, attitude and awareness–questionnaire was developed and validated in 2 phases. In phase I, development and content validation of the questionnaire were done, and in phase II, a pilot study was done on the population for validation, and participants were interviewed using a self-developed questionnaire. Results: The computed content validity index (CVI) for the questionnaire was found to be 0.92. The Cronbach’s Alpha values were determined to be 0.947, 0.909, 0.887, respectively, reflecting strong internal consistency. The overall benchmark is 0.95 which is statistically excellent for validity of outcome Conclusion: The KAAS-SYP, designed to evaluate knowledge, attitude, and awareness about stroke among young populations, demonstrated statistically robust content validity and excellent reliability. While the young population shows an understanding of the term "stroke," there is limited awareness of its risk factors and warning signs. Furthermore, their attitude towards stroke tends to be less positive, highlighting the need for targeted educational and awareness initiatives.